Discovery and Hit to Lead Optimization of Novel Combretastatin A-4 Analogues: Dependence of C-Linker Length and Hybridization - Provot, Olivier; Hamze, Abdallah; Peyrat, Jean-François; Brion, Jean-Daniel; Alami, Mouad (Anti-Cancer Agents in Medicinal Chemistry, 2013)
We have synthesized a large variety of CA-4 analogues having a non-isomerizable C-linker between the A- and B-aromatic rings. Most of them displayed a nanomolar level of cytotoxicity against a panel of human cancer cell lines and inhibited tubulin polymerization at a micromolar level. Among all these compounds, the most interesting compounds were undoubtedly isoCA-4 and structural analogues 18-20 as well as benzil derivatives 11 which displayed a comparable level of activity than that of CA-4. Moreover, it has been demonstrated that these drugs arrested cancer cells in the G2/M phase of cellular cycle and induced apoptosis at very low concentrations. In vitro antivascular effects and the binding mode of the most active compounds was also investigated.
Keywords: linker